Uji Kandungan Formalin pada Sampel Ikan Asin dan Ikan Segar yang Dijual di Pasar Tradisional - Kiki Haetami; Lina Karlina; Junianto Junianto (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2024)
Background: Fish is a commodity that quickly deteriorates and spoils. One method commonly used to extend the shelf life of fish is by storing at low temperatures and salting. However, both methods are relatively expensive, so many sellers prefer to use formalin as a preservative for food products. Aim: This study aims to determine the use of formalin in salted fish and fresh fish in traditional markets. Methode: Testing was carried out qualitatively and quantitatively using the MERCK formalin test kit. Results: Test results on the formalin content of wais salted fish, skinned shark salted fish and salmon from the upper market of Cimahi obtained positive results in all three samples. Each formalin level is 0.10 mg/l; 0.80 mg/l; and 0.25 mg/l. Conclusion: The use of formalin in food products in traditional markets is still carried out by fish sellers. Keywords: Formalin, Salted Fish, Fresh Fish, Traditional Market